Regulatory T Cells: Molecular Actions on Effector Cells in Immune Regulation - Asiel Arce-Sillas; Diana Denisse Álvarez-Luquín; Beatriz Tamaya-Domínguez; Sandra Gomez-Fuentes; Abel Trejo-García; Marlene Melo-Salas; Graciela Cárdenas; Juan Rodríguez-Ramírez; Laura Adalid-Peralta (Journal of Immunology Research)
T regulatory cells play a key role in the control of the immune response, both in health and during illness. While the mechanisms through which T regulatory cells exert their function have been extensively described, their molecular effects on effector cells have received little attention. Thus, this revision is aimed at summarizing our current knowledge on those regulation mechanisms on the target cells from a molecular perspective.